AB0090 Altered expression of pparΓ coactivator 1b in peripheral blood monocytes and synovium from rheumatoid arthritis. (23rd January 2014) - Zhu, L.-J.; Zou, C.-J.; Ma, J.-D.; Zheng, D.-H.; Mo, Y.-Q.; Wei, X.-N.; Dai, L.
Abstract : Background: Rheumatoid arthritis (RA) is a chronic inflammatory disease leading to joint destruction and disability. PPARγ coactivator (PGC) 1β is a transcriptional coactivator that regulates energy metabolism, which strongly upregulated by RANKL during osteoclast differentiation. Knockdown of PGC1β in vitro inhibited osteoclast differentiation, and global PGC1β deletion in mice resulted in increased bone mass. Increased expression of PGC1β protein led to the attenuation of macrophage-mediated inflammation. However, the expression and the pathophysiological role of PGC1β in RA are poorly understood. Objectives: To determine the expression of PGC1β in peripheral blood monocytes (PBMs) and synovium from RA patients. Methods: Synovium was obtained by needle biopsy from 12 patients with active RA, as well as 6 osteoarthritis (OA) and 3 orthopedic arthropathies (Orth.A) as "less inflamed" disease controls. Synovial PGC1β expression was determined by immunohistochemistry staining. PGC1β expression in primary cultured fibroblast-like synoviocyte (FLS) from RA or OA synovium was detected by immunofluorescence staining. PGC1β mRNA expression in PBMs from 16 patients with active RA and 14 age and gender matched healthy controls was detected by real-time PCR. Results: (1) PGC1β expression in RA synovium was observed in lining layer and sublining area with intense nuclear staining in lining synoviocytes and sublining inflammatory cells (Fig 1A ). Synovial PGC1β was over-expressed in RA patients compared with OA or Orth. A patients (Fig 1 ). (2) Immunofluorescence staining showed obviously higher expression of PGC1β in RA-FLS than in OA-FLS (Fig 2 ). (3) PGC1β mRNA expression in PBMs from RA patients was significantly decreased than that in healthy controls (0.60±0.68 vs 1.24±0.81, p=0.005). (4) Spearman's correlation test showed PGC1β mRNA in RA PBMs correlated negatively with RF (r=–0.538, p=0.031) and serum glucose-6-phosphate isomerase (r=–0.515, p=0.041). Fig 1. Representative immunohistochemical findings of synovial PGC1β expression. A, Intensive synovial PGC1β expression in a RA patient; B and C, Mild synovial PGC1β expression in an OA patient and an Orth. A patient. (Anti-PGC1β immunostaining, original magnification, ×400). Fig 2. Immunofluorescence staining of PGC1β in primary cultures of FLS from OA and RA patients. RA-FLS stained significantly positive with PGC1β than OA-FLS (A: OA-FLS, B: RA-FLS; original magnification×400. a, DAPI (blue) ; b, PGC1β (red); c, neutral light; d, merged a, b with c). Image/graph: Conclusions: Our results showed altered PGC1β expression in PBMs, synovium and FLS from RA, which implied that PGC1β may be involved in the pathogenesis of RA synovitis and osteoclastogenesis. More patients and further studies are needed to establish the mechanisms of PGC1β in pathogenesis of RA. Acknowledgements: Supported by Chinese National Natural Science Research Grant (no. 81001334 and 30972742), Guangdong Natural Science Research Grant (no. 10451008901004542 and 9151008901000130), and the Fundamental Research Funds for the Central Universities (no. 10ykpy19). Disclosure of Interest: None Declared